Enhancing clean cooking options in peri-urban Kenya: a pilot study of advanced gasifier stove adoption. (21st July 2020) - Bailis, Rob; Ghosh, Emily; O'Connor, Margaret; Kwamboka, Elvine; Ran, Ylva; Lambe, Fiona
Abstract: Kenya has experienced a decade of relative prosperity with consistent economic growth and minimal political tension. GDP is growing by 3% annually and poverty rates are declining. Despite these gains, Kenya still has a lot of ground to cover to achieve the Sustainable Development Goals (SDGs) by 2030. SDG7, which aims to 'Ensure access to affordable, reliable, sustainable and modern energy for all', exemplifies both Kenya's achievements and the challenges that remain. Access to grid-based electricity and LPG have grown rapidly. However, over 90% of Kenyans still rely on polluting fuels like wood, charcoal and/or kerosene for some or all of their cooking needs. Substantial effort is needed to ensure all Kenyans have access to clean cooking options by 2030. We present the results of a pilot study in which gasifier-based pellet stoves were introduced in 150 peri-urban households. The stoves include an internal fan that improves combustion efficiency and reduces emissions by 90%–99% relative to charcoal and fuelwood in traditional devices. A subset of participants received stoves with 'Pay-as-You-Cook' (PAYC) hardware, which relies on pre-paid RFID card to activate the stove's internal fan, allowing vendors to sell the stove below cost and recoup losses through pellet sales. We find that people were willing to include pellet stoves in their cooking routines and, in many cases, pellets displaced polluting fuels. We also find that PAYC hardware did not negatively impact adoption: PAYC users had higher daily rates of fuel consumption and reported higher willingness to pay for the stove than non-PAYC users. However, stoves were not used exclusively. Instead, people stacked pellets in combination with other cooking options, with pellets contributing to 12%–40% of their cooking needs (inter-quartile range). Though the project did not successfully overcome all of the barriers necessary to achieve long-term adoption of advanced pellet stoves, the results demonstrate that pellets could contribute to a portfolio of cleaner options. Social media abstract: In a pilot project, clean-burning 'pay-as-you-cook' pellet stoves were stacked with LPG and polluting fuels.